Editorial / Éditorial Volume 49 Issue 3 - Martha Cleveland-Innes (The Canadian Network for Innovation in Education (CNIE), 2024)
Welcome to volume 49, issue 3 of The Canadian Journal of Learning and Technology (CJLT). CJLT is a decades-old peer-reviewed journal that invites English or French submissions on the research and practice of education, technology, and learning. This bilingual journal is free-of-charge to anyone with access to the Internet, is multi-indexed, and presented in accessible formats. There are no article submission/publication fees or access charges. CJLT's history dates back to where distance education was an innovation characterized by portable print-based material and non-digital technologies. This issue's Notes section is presented by Dr. Olaf Zwacki-Richter. Here, he reviews the history of distance education with a view to current pressures on teaching and learning. The Origins of the Term Distance Education and the Roots of Digital Teaching and Learning is both articulate and accurate. It provides an inspiring view of new ways to define and use concepts of Open, Distance, and Digital Education (ODDE), based on historical education milestones. This prepares readers with a lens to the research articles which follow.